Future Changes in Tropical Cyclone Activity in High‐Resolution Large‐Ensemble Simulations. Issue 19 (4th October 2017) - Yoshida, Kohei; Sugi, Masato; Mizuta, Ryo; Murakami, Hiroyuki; Ishii, Masayoshi
Abstract: Projected future changes in global tropical cyclone (TC) activity are assessed using 5, 000 year scale ensemble simulations for both current and 4 K surface warming climates with a 60 km global atmospheric model. The global number of TCs decreases by 33% in the future projection. Although geographical TC occurrences decrease generally, they increase in the central and eastern parts of the extra tropical North Pacific. Meanwhile, very intense (category 4 and 5) TC occurrences increase over a broader area including the south of Japan and south of Madagascar. The global number of category 4 and 5 TCs significantly decreases, contrary to the increase seen in several previous studies. Lifetime maximum surface wind speeds and precipitation rate are amplified globally. Regional TC activity changes have large uncertainty corresponding to sea surface temperature warming patterns. TC‐resolving large‐ensemble simulations provide useful information, especially for policy making related to future climate change. Key Points: High‐resolution large‐ensemble simulations are used to assess changes in global tropical cyclone activity under +4 K surface warming Future changes in tropical cyclone activity are investigated in a more objective manner Total number of very intense tropical cyclones decreases contrary to some previous studies, but occurrences increase in several regions